PELATIHAN TEKNIK ELEKTROPLATING NIKEL BAGI INDUSTRI KERAJINAN KUNINGAN DI DESA KAMASAN KABUPATEN KLUNGKUNG - T. G. Tirta Nindhia; I W. Surata; I K. Adi Atmika; D.N.K. Putra Negara; A.A.I.A. Sri Komaladewi; I M. Sucipta (Buletin Udayana Mengabdi, 2013)
The Village of Kamasan at Klungkung in the Province of Bali is recognized as a centre of metal handicrafts,especially the handicraft made from brass. Many home industries for the brass handicraft are established in thisvillage. Recently due to Rapid progress of Tourism in Bali, The brass handicraft in Kamasan are growing wellbecause the demand for the souvenir. However some problem arise such as limited of variation, and surface qualityof the brass handicraft that tend to become blurred or dull due to the process of oxidation. This condition makethe brass handicrafts become not so interest as silver handicrafts that can shine for quite long time. To overcomethis problem it is needed to coating the surface of the brass handicrafts so that there will be no contact withoxygen. The coating will be more benefit if able to exhibit more interesting appearance, as what nickel coatingcan affect the appearance of the surface to become like silver but more clear. Equipment for nickel elektroplatingwas designed for this purpose and donated for this purpose. The unique of the equipment that was donated weresmall in size therefore only low electric power is needed, only 1 liter electrolyte was used and can be use manytime. The positive result is obtained for this activity where all participants able to operate the elektroplatingprocess with excellent result.